Ultrasound‐assisted Extraction with LC–TOF/MS Identification and LC–UV Determination of Imazamox and its Metabolites in Leaves of Wheat Plants. Issue 4 (10th August 2013) - Rojano‐Delgado, Antonia M.; Priego‐Capote, Feliciano; Prado, Rafael De; de Castro, María Dolores Luque; Choi, Young Hae; Verpoorte, Robert
ABSTRACT Introduction imazamox is a herbicide used in many legominous and cereal crops. There are few methods in the literature for determination of imazamox and its metabolites in plants because of the lack of commercial standards or owing to expensive and/or complex synthesis. Objective To develop a method based on liquid chromatography and ultraviolet absorption detection for simultaneous determination of imazamox and its metabolites in plants. Methods Sample preparation was based on ultrasound‐assisted extraction (70 W power and duty cycle of 0.7 s/s for 10 min) with subsequent filtration of the extracts and clean‐up and concentration prior to chromatographic separation and detection at 240 nm. The chromatographic analysis was completed in 30 min using a Luna® HILIC column. Identification and confirmatory analysis of the presence of imazamox and its metabolites in extracts from treated plants was performed by LC–TOF/MS in high resolution mode for precursor ions. The metabolites were quantified using a surrogate approach based on an imazamox standard. The method was validated by analysing wheat samples treated with 200 g per hectare of active ingredient imazamox. Results The linear dynamic range of the calibration curve was within 0.27–600 µg/mL, with a correlation coefficient of 0.998 and precision – studied at 0.1 and 2 µg/mL – of 2.9% and 5.0% for repeatability, and 4.7% and 6.9% for reproducibility, respectively. Conclusion The analytical characteristics of the method make it recommendable for evaluating the metabolism of imazamox in plants. Copyright © 2013 John Wiley & Sons, Ltd.